2020
DOI: 10.3390/ijerph17072357
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Association between Participation in Physical Education and Physical Activity among U.S. High School Students, 2011–2017

Abstract: The purpose of this study was to assess trends in physical education and physical activity among U.S. high school students from 2011 to 2017, respectively, and to evaluate temporal trends in the relationship between physical education class participation and physical activity levels. Data from a total of 51,616 high school students who participated in the Youth Risk Behavior Surveillance System (YRBSS) from 2011 to 2017 were analyzed for this study. Physical education was measured as follows: In an average wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…After a thorough analysis, 16 studies were excluded for the reasons shown in Figure 1 . A total of 43 studies 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 reported evidence relevant to our review (see Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…After a thorough analysis, 16 studies were excluded for the reasons shown in Figure 1 . A total of 43 studies 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 reported evidence relevant to our review (see Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…PE participation has been recoded differently across studies, depending on each study purpose. For example, it has been recoded such as having PE classes on at least 1 day/week [ 9 , 27 ]; on ≥3 days/week and ≥5 days/week [ 25 ]; as the mean number days/week [ 27 ]; as the number of days/week (0, 1, 2, 3, 4, 5) [ 27 , 29 ]; and as never, 1–2 days/week and ≥3 days/week [ 11 ]. Similar to the last study, in the present work, PE participation was recoded into four categories: never, 1–2 days/week, 3–4 days/week and ≥5 days/week.…”
Section: Methodsmentioning
confidence: 99%
“…Worldwide, the estimated global prevalence of adolescents practicing sufficient physical activity (PA) is low [ 1 ]. Given this scenario, the role of schools and physical education (PE) in promoting physically active and healthy lifestyles has been increasingly recognized as an essential component of the endeavours to develop a more active society, both in policy [ 2 , 3 , 4 , 5 , 6 ] and in research [ 7 , 8 , 9 , 10 , 11 ]. Several reasons have been advanced as to why schools and PE are of importance in promoting PA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical education as a physical activity that is part of the educational process that can develop physical fitness, body and intellectual organs as well as emotional control, it is stated as follows: Physical education as an aspect of the overall educational process by emphasizing activities that develop fitness, function organs, neuromuscular control, intellectual strength and emotional control (Ryu et al, 2020). Physical education carried out in schools will help the intellectual formation and development of individuals as social beings.…”
Section: Reconstruction Of Contents Of Article 35 Paragraph 3 Of the ...mentioning
confidence: 99%